Application of shape memory alloy prestressing devices on an ancient aqueduct - Demetriou, Themos; Chrysostomou, Christis; Stassis, Andreas (My University, 2008)
The results of the application of shape memory alloy (SMA) prestressing devices on an aqueduct are presented in this paper. The aqueduct was built in 1747 to provide water to the city of Larnaca and to its port. Because of its importance to the cultural heritage of Cyprus, the aqueduct has been selected as one of the casestudy monuments in the project Wide-Range Non-Intrusive devices toward Conservation of Historical Monuments in the Mediterranean Area (WIND-CHIME). The Department of Antiquities of Cyprus, acting in a pioneering way, have given their permission to apply the devices in order to investigate their effectiveness in providing protection to the monument against probable catastrophic effects of earthquake excitation. The dynamic characteristics of the structure were determined in two separate occasions and computational models were developed that matched very closely the dynamic characteristics of the structure. In this paper the experimental setup and the measured changes in the dynamic characteristics of the monument after the application of the SMA devices are described.
Keywords: Masonry; Monuments; Earthquake hazard analysis